Two new Eulophinae genera (Chalcidoidea: Eulophidae) from the Neotropical region - Hansson, Christer (Zootaxa, 2020)
Two new Eulophinae genera, Elasmarion and Celesterion, are described based on material from sweep-net and malaise trap samples mainly from Costa Rica. The new genera are each represented by a single species, both described here, E. longipes and C. reticulatum spp. nov. The material for both groups is abundant and strongly female biased, 119 females and two males in Elasmarion, and 63 females and two males in Celesterion. Elasmarion is similar to the Old World genus Eulophomorpha Dodd, and a table with distinguishing characters is included, it also has some morphological features similar to the genus Elasmus Westwood. Celesterion does not show close morphological similarity to any genus in the Eulophinae. The biology is unknown for both species.